ChemInform Abstract: Scope of Successive C—H Functionalizations of the Methyl Group in 3‐Picolines: Intramolecular Carbonylation of Arenes to the Metal‐Free Synthesis of 4‐Azafluorenones. Issue 17 (April 2016) - Laha, Joydev K.; Jethava, Krupal P.; Patel, Sagarkumar
Abstract: Various 2‐aryl substituted 3‐picolines are efficiently transformed into 4‐azafluorenes and the products are isolated as single regioisomers.